Attacks on World Central Kitchen Humanitarian Volunteers by Israel from an International Legal Perspective - Pragnyaputra, Bimo Irsyad; Nasyithalillah, Najmi; Riona, Dhyfa Bunga (Andalas Law Journal, 2024)
The prolonged conflict between Israel and Palestine has created a dependence among Gaza's population on humanitarian aid to meet basic needs, including food. World Central Kitchen (WCK), as one of the leading humanitarian organizations, plays a crucial role in providing food assistance in Gaza. However, on April 1, 2024, seven WCK volunteers were killed in an airstrike launched by the Israeli military. This incident triggered international condemnation and raised questions about the protection of humanitarian volunteers under international humanitarian law. This study employs a normative juridical method to analyze the violations of international law committed by Israel, focusing on the 1949 Fourth Geneva Convention, the 1977 Additional Protocols, and the 1998 Rome Statute. The findings of the study indicate that the attack on WCK volunteers constitutes a violation of the principle of distinction in humanitarian law, which prohibits attacks on civilians and civilian objects. Additionally, as a signatory of the Fourth Geneva Convention, Israel has failed to fulfill its obligations to protect humanitarian volunteers, who are considered civilians under international law. The legal implications of this violation include Israel's state responsibility to provide reparations, including restitution, compensation, and satisfaction to the victims and their families. This research also emphasizes the need for more effective enforcement mechanisms to ensure accountability for those who violate humanitarian law. Thus, this study makes an important contribution to strengthening the protection of humanitarian volunteers and advocating for reforms in international law to prevent similar incidents from occurring in the future.